Cenozoic assemblage coccolith size (90th percentile of the Feret extquotesingles diameter) from the Atlantic Ocean - Ruby Barrett; Ann Power (PANGAEA, 2025)
This dataset includes the 90th percentile of the size of coccoliths in the assemblage (Feret extquotesingles diameter; μm) for the Atlantic Ocean Sites DSDP 80-548 and ODP 154-925 and 154-929, spanning the Cenozoic (~0 to 66 Ma). Coccolith size data were acquired from images taken using an ImageStream X MkII flow cytometer with a light polarising filter and include circular-to-oval shaped coccoliths and star-shaped coccoliths. This dataset can be used to investigate how coccolith size of the aforementioned types changes through the Cenozoic.